2011
DOI: 10.1007/s00586-011-1698-5
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic spine fractures: injury profile and outcomes of a surgically treated cohort

Abstract: There are only few reports in literature about the treatment of traumatic lesions of the thoracic spine. They have been grouped together with thoracolumbar fractures, ignoring the particular biomechanics of the thoracic segment. The objective of this retrospective cohort is to describe the clinical presentation and outcomes of surgically treated patients with these injuries. Data were obtained from the institutional database of medical registries, identifying all the patients who had been treated for thoracic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
0
10
1
Order By: Relevance
“…[3] In our series of thoracolumbar SCIs, 72.4% of patients neurologically improved one or more ASIA level after surgery compared with the neurological status at admission. According to literature, this improvement suggests that an early surgical decompression of spinal cord (<24 h since trauma) and posterior stabilization maximize the opportunity of neurological recovery.…”
Section: Discussionmentioning
confidence: 99%
“…[3] In our series of thoracolumbar SCIs, 72.4% of patients neurologically improved one or more ASIA level after surgery compared with the neurological status at admission. According to literature, this improvement suggests that an early surgical decompression of spinal cord (<24 h since trauma) and posterior stabilization maximize the opportunity of neurological recovery.…”
Section: Discussionmentioning
confidence: 99%
“…From Russia it has been reported that 33% of all accidents occurred during gymnastics. [1][2][3][4][5][6] As per report of the International Conference (Spinal Injuries Management, New Delhi, 1995), the incidence of spinal injury was estimated at 15 new cases per million per year in India. This translates into 15,000 new cases per year, and with a backlog of 10 years, the prevalence exceeds 0.15 million.…”
Section: Discussionmentioning
confidence: 99%
“…Minimal encroachment of spinal canal at this level may produce severe deficits. 1,2 We introduce two new peculiar cases of dorsolumbar burst fractures secondary to a peculiar tipper truck injury to the literature.…”
mentioning
confidence: 99%
“…After surgical treatment of thoracic vertebral fractures by posterior stabilization in general, non-surgery-related complications occur in 49%-60%, especially in patients with complete or incomplete paraplegia [28,46]. Deep venous thrombosis is observed in 4%-9% [13,36]-compared to 24.5% in conservatively treated patients [5].…”
Section: Outcome After Posterior Stabilizationmentioning
confidence: 99%